Quantum Imprints on CMBR - Shreya Banerjee (Universe, 2023)
Quantum cosmology aims to develop a quantum theory of the universe, attempting to answer open questions of physical cosmology, mainly related to the early epochs of the universe. Such a theory aims to unite relativity theory and quantum theory. Here, the whole universe is treated as a quantum mechanical system and is described by a wave function rather than by a classical spacetime. In this review, I shall describe the mathematical structure and primary formulations that form the backbone of quantum cosmology. We know that over a period of time, several approaches were developed to form a quantum theory of gravity. However, in order to decide which approach is the best, we need testable predictions, effects that can be observed in cosmic microwave background radiation (CMBR). I shall discuss the methodologies for generating quantum gravitational corrections to inflationary background leading to testable predictions. Another aspect of finding quantum imprints on CMBR results through the application of resolution of the ‘quantum measurement problem’ to early universe physics. In this article, I shall also discuss two such promising models explaining the classicalization of inflationary perturbation and are capable of leaving distinct observational imprints on the observables.